Sosialiasi Cerdas Menghadapi Disinformasi di Era AI dan Media Sosial: Program Pengabdian Masyarakat di Desa Jaharun, Kecamatan Galang Kabupaten Deli Serdang - Siti Maysarah; Revina Maulida; Astri Wulandari; Hilmi Atha Syafiq; Cindy Mei Yana Munthe; Sintia Dwi Anggring (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The rapid development of information and communication technology has transformed the way people access information, interact, and live their daily lives. In this regard, students from the Mathematics Education Study Program at the State Islamic University of North Sumatra conducted "Smart Socialization" during a community service activity in Jaharun A Village, Galang District. The main objective of this community service activity was to increase awareness and understanding among residents of Jaharun A Village, Galang District, regarding the importance of digital literacy in facing the challenges of AI-based disinformation on social media. The implementation methods included initial observation, outreach, and interviews. The results of this activity indicated high community enthusiasm, active participation, and a better understanding of how to use social media wisely and responsibly. This activity successfully built critical public awareness of the importance of verifying information before sharing it and increased local community preparedness for the complex digital information era. This activity is expected to become a model for applicable and sustainable digital literacy education in rural areas.